Pediatric Hashimoto’s thyroiditis: evaluating a rare cause of midline neck swelling - Ankle, N. R.; Rai, Akash; Paladugu, Tejaswini; Mehta, Ayushi; Chaudary, Tharun (International Journal of Research in Medical Sciences, 2024)
The incidence of Hashimoto’s thyroiditis (HT) in childhood reaches its peak between early to mid-puberty. The AIT’s clinical presentation is optimally assessed with thyroid function, as pediatric patients may exhibit a range of thyroid statuses. A 9-year-old female presented to the ENT OPD with a midline neck swelling, and was diagnosed to have HT. This case report discusses the evaluation and relevant management of this disorder.